PENGARUH TINGGI RIB TERHADAP DEFORMASI PADA KOMBINASI FONDASI SARANG LABA-LABA DAN TIANG BOR DENGAN PENDEKATAN ELEMEN HINGGA TIGA DIMENSI - Hamdhan, Indra Noer; Sahib, Yasmin Jihan Fahira (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2021)
Spiders Nest Construction (SNC) is the foundation in the form of flat concrete plates which are reinforced with upright ribs and soil repair between ribs. The KSLL and bored pile are combined to obtain a foundation with high structural rigidity. This study reviews the magnitude of deformation that occurs in the foundation model with a variation of rib height KSLL 1 m, 1.5 m, and 2 m which are varied with 10 bored pile with diameter of 0.6 m in zig-zag configuration with the soil model Mohr-Coulomb and Hardening Soil. In the Mohr-Coulomb soil model the stress state limits are explained using friction angles (Ï†), cohesion (c) and dilatation angles (Ïˆ). In the Hardening Soil model the soil stiffness is explained much more accurately by using three different stiffnesses namely E50 triaxial stiffness, Eur unloading / reloading stiffness and Eoed oedometer stiffness. In contrast to the Mohr-Coulomb model, the Hardening Soil model takes into account modulei dependence on rigidity. This means that all rigidity increases with pressure. Modeling on PLAXIS 3D shows that the most effective deformation occurs on a foundation with a rib thickness of 0.15 with 10 bored pile and a rib height of 1.5 m. The modeling results show the deformation value that occurs in the Hardening Soil soil model with a rib height of 1 m is 17.91 cm, reduced by 31.491% to 12.27 cm when the thickness of the rib is added to 1.5 m. Whereas in the Mohr-Coulomb soil model, the deformation that occurred on the foundation with a rib height of 1 m was 25.43 cm and reduced 48.997% to 12.97 cm when the rib height was added to 1.5 m.